Feasibility Analysis of Scientific Reasoning Skills Instruments for Prospective Science Teachers Using The Rasch Model - Yuni Arfiani; Dwi Yulianti; Masturi Masturi; Sunyoto Eko Nugroho (Universitas Negeri Semarang, 2025)
This study aims to analyze the feasibility of a scientific reasoning ability test instrument for prospective science teachers using the Rasch model. The instrument developed refers to Lawson's Classroom Test of Scientific Reasoning (LCTSR) indicators, focusing on scientific reasoning abilities, including variable control, combinatorial, probability, relational, and proportional thinking. The analysis was carried out using the Rasch Model with the WINSTEPS Version 5.7.3.0 application to test the validity, reliability, and characteristics of the test items. The feasibility test was carried out on 40 multiple-choice questions, tested on 110 test samples. The analysis results showed that 25 of the 40 questions were valid and covered all indicators of problem-solving skills. The test instrument also has a high level of internal consistency with a person reliability value of 0.84 and an item reliability of 0.95. Analysis of the level of difficulty of the test items showed a balanced distribution between very difficult, difficult, moderate, and easy questions. No items were detected as biased, indicating that this instrument is fair and can be used without favoring one group of individuals. Overall, the developed problem-solving skills test instrument is valid and reliable for use on prospective science teachers, assisting educators in evaluating students' problem-solving skills, providing constructive feedback, and improving the quality of learning in science.